Electoral Integrity and Election-Related Conflict. Issue 3 (2nd July 2020) - Linebarger, Christopher; Salehyan, Idean
ABSTRACT: Why are some elections contested with social unrest and protest – sometimes violent – while others pass with little conflict? We focus our study on two types of election, each of which is defined with respect to different types of fraud: "unfree elections, " or those in which elites manipulate electoral laws and institutions, and "unfair elections, " or those in which elites manipulate votes and voters during the campaign. Unfree elections are not correlated with conflict events because the effects of electoral law are felt diffusely and manipulated electoral law is a show of elite strength. Unfair elections, by contrast, provide a highly visible focal point that allows the opposition to mobilize while simultaneously signaling elite weakness. Finally, citizens form expectations about freeness and fairness over time, engaging in conflict behavior when they perceive a deterioration in electoral fairness. We test these expectations on a sample of African, Central American, and Caribbean states during the period 1990–2011. Our findings identify those types of election fraud most likely to correlate with election-related conflict and violence.